Sleep profile predicts the cognitive decline of mild-moderate Alzheimer's disease patients. Issue 10 (10th May 2021) - Targa, Adriano D S; Benítez, Iván D; Dakterzada, Faridé; Carnes, Anna; Pujol, Montse; Jorge, Carmen; Minguez, Olga; Dalmases, Mireia; Sánchez-de-la-Torre, Manuel; Barbé, Ferran; Piñol-Ripoll, Gerard
Abstract: Study Objectives: To investigate the association between sleep and cognitive decline of patients with mild-moderate Alzheimer's disease. Methods: Observational, prospective study, including consecutive patients diagnosed with mild-moderate Alzheimer's disease. Cerebrospinal fluid was collected for amyloid-beta, total-tau, and phospho-tau levels determination. Also, overnight polysomnography was performed, followed by neuropsychological evaluations at baseline and after 12 months of follow-up. Principal component analysis revealed two profiles of patients in terms of sleep: one with a propensity to deepen the sleep (deep sleepers) and the other with a propensity to spend most of the time in the lighter sleep stage (light sleepers). Results: The cohort included 125 patients with a median [IQR] of 75.0 [72.0;80.0] years. Deep and light sleepers did not present differences in relation to the cerebrospinal fluid pathological markers and to the cognitive function at the baseline. However, there was a significant difference of −1.51 (95% CI: −2.43 to −0.59) in the Mini-mental state examination after 12 months of follow-up. Accordingly, sleep depth and cognitive decline presented a dose–response relationship ( p -for-trend = 0.02). Similar outcomes were observed in relation to the processing speed (Stroop words test, p -value = 0.016) and to the executive function (Verbal fluency test, p -value = 0.023). Conclusions: Considering the increased cognitive decline presented by light sleepers, the sleep profile may have a predictive role in relation to the cognitive function of patients with mild-moderate Alzheimer's disease. The modifiable nature of sleep sets this behavior as a possible useful intervention to prevent a marked cognitive decline. Clinical Trial Information: Role of Hypoxia Ans Sleep Fragmentation in Alzheimer's Disease. and Sleep Fragmentation. Completed. NCT02814045